MoU signing ceremony between UiTM, Guangxi Minzu Normal University, China, and Tang Poetry Creative Recitation Competition - UiTM Cawangan Kelantan, Unit Komunikasi Korporat (2022)
MACHANG, 2 November - UiTM Kelantan Branch (UiTMCK) and Guangxi Minzu Normal University (GXMZNU) have agreed to extend the Memorandum of Understanding between the two universities on the 14th of September, 2022. UiTMCK and GXMZNU will continue to collaborate in achieving excellence in the fields of academic, cultural, and scientific thought and personnel as well as student exchange from 2022 to 2025. On the same day, the Department of International Affairs (DIA), and Akademi Pengajian Bahasa (APB) UiTM Kelantan Branch (UiTMCK) jointly organised the "Tang Poetry Creative Recitation Competition". A number of 20 finalists from UiTMCK and GXMZNU consisting of students from these two universities were selected to participate in this competition which was co-organised by Akademi Pengajian Bahasa, UiTMCK and Faculty of Foreign language Studies, GXMZNU. The participants were required to recite classical Chinese poems of The Tang Dynasty. The competition was held online via Zoom Meeting and the UiTMCK Official YouTube channel.